2017
DOI: 10.3201/eid2304.161987
|View full text |Cite
|
Sign up to set email alerts
|

Acute Tetraplegia Caused by Rat Bite Fever in Snake Keeper and Transmission of Streptobacillus moniliformis

Abstract: We report acute tetraplegia caused by rat bite fever in a 59-year old man (snake keeper) and transmission of Streptobacillus moniliformis. We found an identical characteristic bacterial pattern in rat and human samples, which validated genotyping-based evidence for infection with the same strain, and identified diagnostic difficulties concerning infection with this microorganism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Recently, Eisenberg et al reported acute tetraplegia in a snake keeper in relation to RBF. The patient’s condition was so bad that he was sedated, mechanically ventilated and even admitted to the intensive care unit [12]. Endocarditis is the primary cause of death, accounting for up to 53% of cases of morality [9, 13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Eisenberg et al reported acute tetraplegia in a snake keeper in relation to RBF. The patient’s condition was so bad that he was sedated, mechanically ventilated and even admitted to the intensive care unit [12]. Endocarditis is the primary cause of death, accounting for up to 53% of cases of morality [9, 13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…PubMed was searched for the following terms: Spirillum minus, Streptobacillus moniliformis, Haverhillia multiformis, rat bite fever, AND osteomyelitis, discitis. Our literature review uncovered associated with S. moniliformis, only 4 cases of osteomyelitis, 1 of possible osteomyelitis, and 4 of discitis, reported globally [6][7][8][9][10][11][12][13][14]. It is difficult to judge in our case whether the findings on MR imaging represent discitis or rather extension of infection from the L2-L3 endplate.…”
Section: Discussionmentioning
confidence: 77%
“…Our patient had a fever, rash, and vomiting at presentation. Patients may also present with more serious conditions, such as disturbed consciousness [ 8 ], which might lead to several types of critical complications, including spinal epidural abscess [ 9 ], mitral valve endocarditis and septic arthritis [ 10 ], acute tetraplegia [ 11 ], and vertebral osteomyelitis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%